2017
DOI: 10.1136/jech-2016-208283
|View full text |Cite
|
Sign up to set email alerts
|

Parallel contagion phenomenon of concordant mental disorders among married couples: a nationwide cohort study

Abstract: BackgroundThe aggregation of mental disorders in couples, as reported by prior research, indicates the effect of familial environments and warrants attention. However, the concordant categories of mental disorders in couples remain unclear. This study investigated spousal concordance for the category of mental disorders among couples throughout Taiwan by using factors associated with such disorders.Methods5643 couples in the 2002–2013 Taiwan National Health Insurance Research Database were analysed and compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 44 publications
0
24
1
Order By: Relevance
“…Some studies suggest that caregiving can increase the risk for some chronic conditions, including heart disease, although some studies find no effect (7,19,20). Evidence also indicates that spouses and partners have similar perceived health and disability status, which might result from shared environments (21)(22)(23). Regardless, whether caregiving contributes to the development of chronic health conditions or reflects common risk factors, caregiving might affect chronic disease management.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that caregiving can increase the risk for some chronic conditions, including heart disease, although some studies find no effect (7,19,20). Evidence also indicates that spouses and partners have similar perceived health and disability status, which might result from shared environments (21)(22)(23). Regardless, whether caregiving contributes to the development of chronic health conditions or reflects common risk factors, caregiving might affect chronic disease management.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the previous similar studies investigated the spousal concordance pattern, i.e., the husband-wife association, for lifestyle factors and selected diseases separately. Some reported that there was spousal concordance of cancer [33]; depression [34]; mental disorders [35]; physical frailty [36]; and metabolic components, including overweight/obesity [16,17,34], diabetes [18][19][20]34,37], dysglycemia [17,34], and hypertension [12,16,21,22] among couples. However, one Japanese study revealed that spousal concordance in metabolic components was weak and modest [38].…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the APIM, the other cause of each person’s Y variable is not the partner’s X variable, but the partner’s Y variable. As one example, the MIM framework is useful to investigate marital satisfaction because of the reciprocity of this concept in relationship researches [ 25 , 26 ]. The details of the method of estimation for MIM are discussed in Ref [ 10 , 27 ].…”
Section: Methodsmentioning
confidence: 99%